DAMPAK KERJASAMA LUAR NEGERI OLEH PEMERINTAH DAERAH TERHADAP PENINGKATAN KEAMANAN EKONOMI (Studi Kasus: Implementasi Program Saemaul Undong di Provinsi Yogyakarta) - Fadhlan Nur Hakiem; Novi Rizka Amalia (UNIDA Gontor, 2021)
This research aims at explaining the impact of international cooperation on economic security. This impact is expected to be illustrated through the implementation of the Program of Saemaul Undong. The program is an international cooperation between Yogyakarta Province and Gyeongsangbuk-do Province, South Korea. The research method used in this research was the Mixed Methods done through the triangulation technique. The object of research was the society in Bleberan village, Gunung Kidul Regency, and Sumbermulyo village, Bantul Regency. The technique of data collection implemented in this research were literature review, in-depth interviews, and survey. The technique of data analysis in this study was to perform data reduction, data categorization, synthesis, and formulating working hypotheses. The results recognized that the Saemaul Undong Program had an impact on economic security. This program has provided increased economic security. However, this research has also shown that this impact was not significant. It is because economic growth has not been evenly distributed. Therefore, it can be concluded that international cooperation was able to provide benefits to economic security.